IMPLEMENTATION OF MAQASHID AL-SHARIA IN DIGITAL HAJJ SAVINGS: INCLUSIVE HAJJ FINTECH IN ISLAMIC BANKING - Mujtahidah, Fikarul; Yazid, Muhammad (I-Economics, 2025)
The development of fintech and digitalization in indonesia provides opportunities for financial product innovation in line with the concept of maqashid al-syariah. This study aims to analyze the implementation of BSI's digital hajj savings product services and their relevance in strengthening the five dimensions of maqashid al-syariah. This study uses a descriptive qualitative method with a library research approach through literature analysis sourced from academic journals, books, and the official websites of OJK and BSI. The findings of this study indicate that the application of fintech in digital hajj savings has fulfilled the five main dimensions of maqashid al-syariah, namely hifdz al-din (religion) supported by the availability of online hajj account opening and siskohat integration, hifdz al-nafs (soul) is strengthened by youth hajj savings that can guarantee readiness when performing hajj and digital financial transparency that can reduce customers' mental concerns, hifdz al-aql (reason) facilitated through the young hajj literacy program and automatic notifications that can help customers make smart decisions, hifdz al-nasl (descendants) is realized through the young hajj savings product, which functions to secure a hajj quota for descendants who are still underage, and hifdz al-mal (wealth) through the mudharabah agreement that generates benefits and is free of administrative costs, thus enabling wealth to be managed well and optimally. The conclusion shows that hajj fintech is a strategic tool based on maqasid al-syariah for the sustainable development of Islamic and inclusive banking in the digital era